2011
DOI: 10.1136/emermed-2011-200481
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of radiation exposure in common radiological investigations: a comparison between radiologists and non-radiologists

Abstract: Background Radiological examinations are commonly requested for patients to aid clinical diagnosis. However, many doctors do not realise how much radiation dosage their patients are exposed to during radiological investigations. This study aims to assess and compare the knowledge of radiologists and non-radiologists about radiation doses of common radiological investigations. Methods A prospective questionnaire study of doctors about the dosage of commonly performed radiological investigations in a university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 13 publications
(10 reference statements)
3
65
2
2
Order By: Relevance
“…There are concerns not all GPs appreciate the levels of radiation dose involved in a CT scan. Several studies have found specialists and GPs inaccurately estimate specific or relative CT doses in comparison to chest x-rays [3337]. A systematic review of physician surveys found CT dose underestimations in a very high proportion of physicians (60-99%) [33].…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns not all GPs appreciate the levels of radiation dose involved in a CT scan. Several studies have found specialists and GPs inaccurately estimate specific or relative CT doses in comparison to chest x-rays [3337]. A systematic review of physician surveys found CT dose underestimations in a very high proportion of physicians (60-99%) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Given clinicians’ knowledge gaps regarding radiation exposure from imaging studies22–26 and the costs of these tests,27–30 displaying this information at clinician order entry may represent an important teaching opportunity regardless of the impact on clinician ordering. Clinicians often underestimate the radiation exposure associated with common imaging studies,25 31 32 and prior research studies suggest that clinicians are interested in learning more about radiation exposure from imaging studies and the costs of medical care 33 34. Previous studies have called for methods to deliver this critical clinical information to physicians, and this study demonstrates that displaying radiation exposure information at electronic order entry may be an acceptable strategy.…”
Section: Discussionmentioning
confidence: 75%
“…In other studies 12 13 assessing the knowledge of non-radiological physicians, ∼ 34% of them correctly estimated the effective dose from a thoracic CT scan. In contrast, another study 20 showed inadequate knowledge among radiologists, but more so among non-radiologists. In our study, radiologists produced the highest percentage of correct dose estimates in all the imaging tests, although their knowledge was not as good as expected.…”
Section: Discussionmentioning
confidence: 90%